Competing Flow Between Partial Circulatory Support and Native Cardiac Output: A Clinical Computational Fluid Dynamics Study. Issue 5 (September 2018) - Engelke, Jennifer; Karmonik, Christof; Rengier, Fabian; Partovi, Sasan; Popov, Aron-Frederik; Osswald, Anja; Arif, Rawa; Schmack, Bastian; Raake, Philip; Simon, André R; Doesch, Andreas; Weymann, Alexander; et al.
Abstract : Partial circulatory support is a promising concept for the treatment of heart failure patients. A better understanding of induced hemodynamic changes is essential for optimizing treatment efficacy. Computational fluid dynamics (CFD) is an alternative method to gain insight into flow phenomena difficult to obtain in vivo . In 10 patients implanted with a Circulite Synergy Micro-pump (HeartWare, Framingham, Massachusetts) (a continuous flow partial circulatory assist device connecting the left atrium to the right subclavian artery), transient CFD simulations were performed. Patients were divided into two groups depending on their cardiac output (CO; high CO group: 5.5 ± 1.1 L/min, low CO group: 1.7 ± 0.7 L/min). The partial assist device provided a supporting flow of 1.5 ± 0.8 L/min. Support was highest at diastole and decreased during systole because of a collision of the blood flows from the partial assist device and the CO. Reversed flow counteracting the flow of the device was significantly higher for the high CO group (mean flow in peak systole: −2.18 ± 1.08 vs. 0.23 ± 0.59 L/min; p = 0.002) showing an inverse correlation between CO and amount of reversed flow during peak systole ( R = −0.7; p < 0.02). The flow collision lead to higher total pressures at the point of collision and consequently in the Circulite outflow graft. The CFD simulations allow quantifying hemodynamic alterations in patients with partial support consisting of a flow collision, thereby reducing effectiveness of the circulatory support. Partial support in heart failure patients alternates their hemodynamics not only in providing support for the circulation but also inducing unfavorable changes in flow patterns.